Development and Evaluation of Amoxicillin Loaded Carbopol 934P Mucoadhesive Microcapsules for Sustained Drug Release for H. pylori Treatment: Amoxicillin mucoadhesive microcapsules - Paul, Bolai; Adimoolam, Senthil; Qureshi, Mohd Javed (Iranian Journal of Pharmaceutical Sciences, 2019)
Amoxicillin (α-amino-p-hydroxybenzyl-penicillin) is a semi-synthetic, orally absorbed and widely prescribed β-lactam antibiotic. It is now widely used for eradication of gastric Helicobacter pylori infection combined with a second antibiotic and an acid‐suppressing agent despite its short elimination half-life of one hour. The purpose of this study was to develop and evaluate amoxicillin loaded carbopol 934P mucoadhesive microcapsules for sustained drug release at the gastric mucosa to prolong the residence time of dosage form in the stomach and to achieve controlled drug release for more effective H. pylori eradication. Amoxicillin mucoadhesive microcapsules were formulated by ion gelation technique using 32 factorial designs. A 32 full factorial design was used to derive the statistical equation, ANOVA analysis, contour plots and 3D response surface plots. FT- IR (4000 cm-1- 450 cm-1) analysis of amoxicillin and with polymers was performed by using potassium bromide pellet method. Different polymer ratios of carbopol 934P and sodium alginate were used to formulate by nine formulations (F1 to F9) amoxicillin mucoadhesive microcapsules. The prepared formulations were characterized by determining their percentage of yield, particle size, percentage of entrapment efficiency,swelling index, percentage of mucoadhesion and percentage of drug release. Amoxicillin and used polymers are found to be compatible with no interaction reported by FTIR analysis. The optimized formulation (F9) exhibited a high drug entrapment efficiency of 96.04±0.03%, particle size of 847.2518±0.06 μm, yield of 98.86±0.01%, swelling index of 120.09±0.06%, and mucoadhesion of 67.00±0.02 after 8 h. A successful sustained drug release was achieved for more than 14 h. In-vitro dissolution test for optimized formulation (F9) demonstrated a slower release behavior in 0.1N hydrochloric acid followed by linear release profile in pH 7.4 phosphate buffer. The drug-to-polymer-to-polymer ratio had a more significant effect on the dependent variables. The release kinetic study of optimized formulation (F9) displayed a good fitting with zero order behavior and Korsmeyer-Peppas model has confirmed a non-Fickian release. The developed mucoadhesive amoxicillin microcapsules were observed to have adhered strongly with gastric mucosa with approximately 14 h of prolonged stay expecting improved bioavailability and reduced dosing frequency and subsequently improving patient’s compliance. The concentration of carbopol 934P and sodium alginate had highly significant effects on depended variables. The present study concludes that amoxicillin mucoadhesive microcapsules can be effectively used for the more effective treatment of H. pylori infection.